Cherubism with peripheral reparative giant cell granuloma in the mandible and maxilla - Sukawijaksa, Hendra; Arindra, Pingky Krisna; istadi, Didit; Haryosuwandito, Erdananda; Lutfianto, Muhammad Bakhrul (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Cherubism is an autosomal dominant disease that causes abnormal osteoblast-osteoclast function, resulting in progressive enlargement around the maxillofacial area due to replacement of normal bone with fibrous tissue and immature bone. The clinical and radiographic signs of cherubism include bilateral radiolucent multi-ocular lesions of the mandible and maxilla, causing bilateral cheek swelling. A 9-year-old boy came to the Oral Surgery of Sardjito Hospital, Yogyakarta, with a complaint of enlargement of both cheeks nine months ago. The patient complained that the swelling on the maxilla enlarged and felt disturbing for his appearance. The enlargement was painless, not easy to bleed, hard, and disturbing when eating and sleeping. Radiograph examination demonstrated bilateral maxillary and mandibular multi-ocular-radiolucent lesions. Three stages of surgery were performed: biopsy-incision with the histopathological result being benign fibrous histiocytoma, curettage-reshaping of the mandible 1 month after biopsy, and curettage-reshaping of the maxilla 9 months after the mandible surgery. The histopathological test of the lesions in the maxilla and mandible showed the same result: peripheral reparative giant cell granuloma. Twelve months postoperatively, the patient had no complaints, showed no disturbances in eating and sleeping, and regained a symmetrical face. The patient's initial curettage and reshaping resolved the masticatory complaints, improved facial aesthetics, and reduced lesions' expansion at the bilateral mandibular and maxillary bones.